HUMAN APPEARANCE as a liguo-cultural concept - Валюкевич, Тетяна Вікторівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article presents the results of cognitive-discursive analysis of the content and structure of the concept HUMAN APPEARANCE. Appearance is defined as a combination of characteristics perceived visually. Human appearance is a whole image and which is perceived as a gestalt. Human appearance presents a value, thus the concept under consideration has an evaluative component in its structure and can be analyzed within linguo-cultural approach. The evaluative component is verbalized by the identifying adjectives, which render sensory, sublime and rationalistic types of evaluation depending on standards set by the society. The adjectives are glossed on the evaluation scale. The image component is viewed as the range of the metaphor as well as cognitive transformations of its correlates.